Rotational (de)-excitation of HMgNC in collision with He. Issue 1 (23rd June 2021) - Amor, M A; Hammami, K; Wiesenfeld, L
ABSTRACT: Potential energy surface (PES) for the collision between HMgNC and He are evaluated using the high-accuracy CCSD(T)-F12 ab initio method. This PES leads to conduct quantum dynamical scattering calculations of the rotational and hyperfine (de)-excitations rate coefficients for temperatures up to 200 K. In order to evaluate the impact of the computed data, we performed radiative transfer computations of the brightness and excitation temperatures for selected observed j = 8 – 7 transition.